Taṭwīr al-Tadrībāt al-Lughawiyyah al-‘Arabiyyah bi-Istikhḍām al-Al‘āb al-Tafā‘uliyyah Wordwall - Ummah, Khaira; S, Yelfi Dewi (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This Research and Development (R&D) study aims to innovate interactive Arabic language exercises through the Wordwall platform to address the limitations and monotony of traditional instructional methods at Jam'iyatul Hujjaj Primary School. The study adopted the ADDIE instructional design model, encompassing five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with a sample of 30 third-grade students, utilizing observation, interviews, questionnaires, and pre- and post-tests as primary data collection instruments. The results indicate that the developed exercises achieved high validity ratings (78%–80%) based on expert validation and demonstrated excellent practicality scores (90%–98%) among both students and the teacher. Furthermore, quantitative analysis confirmed the product's effectiveness in improving linguistic performance, as evidenced by an average N-Gain score of 0.83, which categorizes the intervention as